2006
DOI: 10.2337/diacare.29.04.06.dc05-1938
|View full text |Cite
|
Sign up to set email alerts
|

α2-Heremans-Schmid Glycoprotein/ Fetuin-A Is Associated With Insulin Resistance and Fat Accumulation in the Liver in Humans

Abstract: OBJECTIVE -The ␣ 2 -Heremans-Schmid glycoprotein (AHSG; fetuin-A in animals) impairs insulin signaling in vitro and in rodents. Whether AHSG is associated with insulin resistance in humans is under investigation. In an animal model of diet-induced obesity that is commonly associated with hepatic steatosis, an increase in Ahsg mRNA expression was observed in the liver. Therefore, we hypothesized that the AHSG plasma protein, which is exclusively secreted by the liver in humans, may not only be associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
414
3
19

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 448 publications
(470 citation statements)
references
References 23 publications
34
414
3
19
Order By: Relevance
“…Our study demonstrated that serum fetuin-A was related to IR, and HOMA2IR index and fasting insulin serum levels were increased; this result is consistent with previous results (4,(22)(23)(24). Therefore, fetuin-A may be used as a new factor implicated in T2DM pathology and physiology; IR also plays an important role in the T2DM mechanism (25).…”
Section: Original Articleesupporting
confidence: 81%
“…Our study demonstrated that serum fetuin-A was related to IR, and HOMA2IR index and fasting insulin serum levels were increased; this result is consistent with previous results (4,(22)(23)(24). Therefore, fetuin-A may be used as a new factor implicated in T2DM pathology and physiology; IR also plays an important role in the T2DM mechanism (25).…”
Section: Original Articleesupporting
confidence: 81%
“…Stefan et al 161 reported that a-2HSG is associated with insulin resistance and fat accumulation in the liver in humans, which may link it with the alteration in apolipoproteins found in this study. Until now, however, there has been no published data correlating schizophrenia and a-2HSG.…”
Section: Immune Responsementioning
confidence: 65%
“…Most reported concentrations were obtained from Specialty Laboratories (www.specialtylabs.com). The remaining reported concentrations were obtained from the literature as referenced: interleukin-3 28 ; CSF1 29 ; PLAU 30 ; beta-enolase 31 ; enolase 1, alpha 32 ; IGF1 33 ; uromodulin 34 ; lactotransferrin 35 ; HGFAC, serum amyloid A protein, IGFALS, factor XII, apolipoprotein C-II 4 ; beta-2-microglobulin 36 ; PROZ 37 ; protein C 38 ; apolipoprotein D 39 ; apolipoprotein C-III 40 ; vitamin D-binding protein 41 ; alpha-2-HS-glycoprotein 42 ; hemopexin. 43 teins were common to both data sets and corresponded to 25.6% of the proteins identified in the liver tissue and to 38.5% of the proteins identified in plasma (Fig.…”
Section: Resultsmentioning
confidence: 99%